2013
DOI: 10.1177/2158244013491406
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Use of Condoms Among Sexually Active Youth in Southern Highlands, Tanzania

Abstract: Sexual behavior change is a complex issue influenced by complex variables, intrinsic and extrinsic. This study aimed to assess factors influencing actual use of a male condom among secondary school students in southern Tanzania. In all, 227 sexually experienced participants aged 14 to 18 completed a pretested questionnaire. Out of 227 sexually active participants, 120 (53%) reported consistent condom use and (62.5%) had multiple sexual partnerships. Of 120 who reported condom use, 42 (35%) had tested for HIV. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 27 publications
3
31
2
Order By: Relevance
“…Sexual behaviour of adolescents is shaped by multiple factors [ 1 , 4 , 24 ] which either act at individual level such as knowledge and attitudes or those which result as a consequence of the surrounding environment (ecological factors) such as availability of condoms and policies that create favourable environment to use condoms [ 20 , 24 – 26 ]. In an attempt to understand sexual behaviour several theories and models have been applied in past research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual behaviour of adolescents is shaped by multiple factors [ 1 , 4 , 24 ] which either act at individual level such as knowledge and attitudes or those which result as a consequence of the surrounding environment (ecological factors) such as availability of condoms and policies that create favourable environment to use condoms [ 20 , 24 – 26 ]. In an attempt to understand sexual behaviour several theories and models have been applied in past research.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the existing evidence is devoted to isolated theories or combination of theories that target a group of factors which act at the same level and therefore they may not be sufficient to understand the complexities of the sexual behaviours among adolescents. Studies in Tanzania and elsewhere in SSA, have focused much on socio-cognitive theories alone, such as the Health Belief Model [ 21 , 26 ] and the Theory of Planned Behaviour (TPB) [ 15 , 30 ]. In order to understand the complexities of sexual behaviour and thereby device comprehensive programs to improve safe sexual behaviour among adolescents, there is a need for integrated approach.…”
Section: Introductionmentioning
confidence: 99%
“…4 This finding is in contrast with findings from previous investigators on youth's sexual activity in Tanzania, who found that condom use was higher among older respondents. 4,16 Marital status was associated with unprotected sex, multiple concurrent sexual partnerships, and marijuana use. The likelihood of condom use was higher among unmarried participants than their married counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with behavioural studies assessing motivating factors associated with condom use among youth, which found that respondents who perceived higher susceptibility to HIV infection through their risky behaviours were more likely to report condom use. 5,16 Transactional sex was associated with unprotected sex, having multiple concurrent partners, and marijuana use. Porters who reported to have paid and/or received money or a gift in exchange for sex were more likely to report unprotected sex and to smoke marijuana.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation